x+5+6=4(1-3x)-4(1-6x)

Simple and best practice solution for x+5+6=4(1-3x)-4(1-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+5+6=4(1-3x)-4(1-6x) equation:


Simplifying
x + 5 + 6 = 4(1 + -3x) + -4(1 + -6x)

Reorder the terms:
5 + 6 + x = 4(1 + -3x) + -4(1 + -6x)

Combine like terms: 5 + 6 = 11
11 + x = 4(1 + -3x) + -4(1 + -6x)
11 + x = (1 * 4 + -3x * 4) + -4(1 + -6x)
11 + x = (4 + -12x) + -4(1 + -6x)
11 + x = 4 + -12x + (1 * -4 + -6x * -4)
11 + x = 4 + -12x + (-4 + 24x)

Reorder the terms:
11 + x = 4 + -4 + -12x + 24x

Combine like terms: 4 + -4 = 0
11 + x = 0 + -12x + 24x
11 + x = -12x + 24x

Combine like terms: -12x + 24x = 12x
11 + x = 12x

Solving
11 + x = 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
11 + x + -12x = 12x + -12x

Combine like terms: x + -12x = -11x
11 + -11x = 12x + -12x

Combine like terms: 12x + -12x = 0
11 + -11x = 0

Add '-11' to each side of the equation.
11 + -11 + -11x = 0 + -11

Combine like terms: 11 + -11 = 0
0 + -11x = 0 + -11
-11x = 0 + -11

Combine like terms: 0 + -11 = -11
-11x = -11

Divide each side by '-11'.
x = 1

Simplifying
x = 1

See similar equations:

| 9+7=20-x | | -4(x+6)=6(1-x)-4x | | r^2-r=36+4r | | 4x+7=3x-2 | | 7(1-2x)-8(x+2)=-5x-8x | | 5x+8y=-32 | | -5(x-4)=2(-2x+5)-5 | | 3(x-7)=12 | | 3(5n-3)=-(n-7) | | x^3-5x^2=36x | | x^2-(x+25)=(x+2)(x-2) | | -3(1-2n)-7n=-6-8(n+4) | | (x-3)(x^2-3x+9)=0 | | 2m^2+10=0 | | -49-35x=7(-5x+8) | | 2x^3+(-13x^3)=x | | 2(x^2-5)=2x^2+x-50 | | -(1-6x)=-2(-3x+3) | | 2(8+7r)=6(2+3r) | | 3x+5= | | 5(x-3)-(x-5)=x-1+1+2x | | -3(x+6)-6x=-2(1+5x) | | 7=2+5(z-2) | | 2x+8x=2(x+1)+5(8x+6) | | 12x+23=5x+205 | | 4(2+n)=-2(n+4)+4 | | 161-4x=23x+23 | | 4(2+n)=-2(n+4 )+4 | | 7-8x=22-15x | | 4(2+n)=-2(1+5n) | | -155-8x=9x+15 | | 2+10x=92+x |

Equations solver categories